Designing a Traceability System for Rice Distribution Process Using QR Code Bassed Android Application at Perum Bulog Subdivre III Surakarta - Afan Sutopo; Susy Susmartini; Lobes Herdiman (Jurnal Ilmiah Teknik Industri, 2021)
The state-owned Enterprises (SEO) that manages businesses in the food sector, especially rice is Perum Bulog. However, there were often reports from public about quality of Perum Bulog's rice. Such as the rice had contaminated with gravel or plastic and did not match with premium rice standard. Moreover, The distribution process of premium rice to outlet (RPK) found uncertainty over the arrival time of orders. It caused out of stock and lost sales at the outlet. This paper introduces a q traceability system rice distribution process based on Android with QR Code technology. Furthermore, this paper discusses the system architecture and the development of traceability system design using the company's business process data flow diagram. The developed prototype system shows the functional requirements of the system and can be used by stakeholders to monitor the production process and assist the decision-making process.